Changing Climates, Earth Systems and Society - Dodson, John.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
The book covers state-of-the-art considerations on how climate change has and will deliver impacts on major globalised biophysical and societal themes that will affect the way the world functions. Human activity has resulted in changes to atmospheric chemistry and land cover, and caused serious decline in biodiversity. Modifying biogeochemical cycles leads to complex feedbacks. The future climate will have impact on food security and agriculture, water supply and quality, storm and cyclone frequency, shoreline stability, biodiversity and the future of biological resources. Earth scientists might be asked to forecast any potential abrupt or environmental surprises. A sound knowledge of the Earth System will improve the chances of achieving this, by developing climate models that will reduce the degree of uncertainty in regional climate prediction. This volume sets out a framework of research issues that show how the Earth sciences contribute to a better understanding of climate change and suggests where future research will best contribute to the wellbeing of society. The key topics discussed are: - climate change patterns over the last four glacial cycles; - the variability in climate over the last 1000 years; - impact that past climate change has had on societies; - the role of human activities in climate forcing; - the role of models in predicting future climate and how we can assess their merit; - the future and likely future climate trajectories.
Setting the Scene: How Do We Get to a Fitting Future? -- Impacts of Climate Change on Terrestrial Ecosystems and Adaptation Measures for Natural Resource Management -- Fire in the Earth System -- Vanishing Polar Ice Sheets -- Climate and Peatlands -- Climate and Lacustrine Ecosystems -- Rivers -- Climate Change and Desertification with Special Reference to the Cases in China -- Climate Change, Societal Transitions and Changing Infectious Disease Burdens -- Don$1 (Bt We All Want Good Weather and Cheap Food? -- Building Capacity to Cope with Climate Change in the Least Developed Countries -- Climate Change Mitigation Policy: An Overview of Opportunities and Challenges.s
Keywords: Environment; Climate change; Atmospheric sciences; Physical geography; Environment; Climate Change; Environment, general; Atmospheric Sciences; Climate Change Management and Policy; Physical Geography; Electronic books